Integration of social issues in social studies learning to improve understanding of the concept of social problems - Adawiyah, Siti; Yani, Dwi; Alyanti, Siti Elni; Rustini, Tin (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2023)
Social studies can be used as a subject that can improve students' abilities; social sensitivity. In this way, not only cognitive intelligence increases, but also attitudes and skills. The aim of this research is to describe social problems in social sciences (IPS) learning which are still relevant and contextually relevant today. This research uses a qualitative descriptive research method. Data collection was carried out using library research. In this regard, social studies teaching materials examine social problems that are currently developing, namely the issue of peace and development. The hope is that through social learning it can shape students into good and responsible citizens. The formation of peace agents should not only be aimed at adults, but students can be trained to become world peace agents.